The helminth community of a population of Rattus norvegicus from an urban Brazilian slum and the threat of zoonotic diseases. Issue 6 (8th November 2017) - Carvalho-Pereira, Ticiana; Souza, Fábio N.; Santos, Luana R. N.; Walker, Ruth; Pertile, Arsinoê C.; de Oliveira, Daiana S.; Pedra, Gabriel G.; Minter, Amanda; Rodrigues, Maria Gorete; Bahiense, Thiago C.; Reis, Mitermayer G.; Diggle, Peter J.; et al.
Abstract: Urban slums provide suitable conditions for infestation by rats, which harbour and shed a wide diversity of zoonotic pathogens including helminths. We aimed to identify risk factors associated with the probability and intensity of infection of helminths of the digestive tract in an urban slum population of Rattus norvegicus . Among 299 rats, eleven species/groups of helminths were identified, of which Strongyloides sp., Nippostrongylus brasiliensis and, the human pathogen, Angiostrongylus cantonensis were the most frequent (97, 41 and 39%, respectively). Sex interactions highlighted behavioural differences between males and females, as eg males were more likely to be infected with N. brasiliensis where rat signs were present, and males presented more intense infections of Strongyloides sp. Moreover, rats in poor body condition had higher intensities of N. brasiliensis . We describe a high global richness of parasites in R. norvegicus, including five species known to cause disease in humans. Among these, A. cantonensis was found in high prevalence and it was ubiquitous in the study area – knowledge which is of public health importance. A variety of environmental, demographic and body condition variables were associated with helminth species infection of rats, suggesting a comparable variety of risk factors for humans.